The mechanism of sugar produced from simple glycolaldehyde derivative at ambient conditions. Issue 7 (8th December 2021) - Zhao, Yanliang; Wang, Honglei; Wu, Naiwei; Yang, Junxia; Sun, Jikai; Zhai, Dong; Deng, Weiqiao
Abstract: A benchmark of sugar produced from simple glycolaldehyde derivative has been achieved at ambient conditions ( Science, 2004, 305, 1752 ), which is the most important step to produce life in nature. However, the mechanism has never been clearly understood. Here, we report a reaction mechanism which includes a two‐step synthesis of sugars by selective aldol reactions based on the density functional theory (DFT) calculations. Results show that the prochirality of attacking orientation of the enamine intermediate and steric effect in proton transfer is the main cause for stereochemical preference. This work provides the theoretical insight of sugar produced in glycolaldehyde procedure and may assist the improvement of catalyst design for this procedure. Abstract : The mechanism of sugar produced from simple oxyaldehyde at ambient conditions was investigated by the density functional theory (DFT) calculations. The prochirality of attacking orientation of the enamine intermediate and steric effect in proton transfer determine the selectivity.